The located making framework for supporting craft maker enterprises in China. (24th October 2022) - Walker, Stuart; Evans, Martyn; Zhang, Wanlin; Humphreys, Peter
Abstract: This paper presents the Located Making Framework to support small maker enterprises in China who employ craft making practices by helping ensure (a) they are fully utilising local support opportunities; (b) their decision-making aligns with the fundamental values driving the enterprise; (c) they align with principles of sustainability; and (d) design opportunities are identified. Using constructivist methods (observations, interviews etc.), primary data was collected in the Yellow River Valley region, coded and analysed, and values and context-relationships interpreted from results. This framework, adapted to the Chinese context, is the latest iteration of a model initially developed from our research in the USA and the UK. The Chinese findings are shown in specially developed graphic formats that are readily understandable and lend themselves to ease of use. Future work to increase the reach of the research includes development of an online interactive framework to automatically generate individual and cumulative results.